2021
DOI: 10.3390/ijerph18094901
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, HIV-Related Characteristics, and Health Care Factors as Predictors of Self-Reported Vaccination Coverage in a Nationwide Sample of People Aging with HIV in Germany

Abstract: Preventing infectious diseases through vaccination becomes more significant among the growing population of people aging with HIV. Coverage rates for vaccinations and factors associated with vaccination utilization among this population in Germany are unknown. We assessed the coverage of eight recommended vaccinations in a certain time frame in our convenience sample of 903 people living with HIV aged 50 years and older. We analysed coverage rates and used bivariate and multiple linear regression analyses to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
2
3
0
1
Order By: Relevance
“…For the behavioral skill construct, lack of self-confidence and/or skills to talk about HPV vaccination with sexual partners, relationships with sexual partners, and partners’ vaccine hesitancy were key factors. In addition, issues related to procurement of the vaccine, including perceived unavailability or inaccessibility, were barriers to vaccine uptake; barriers specifically related to transportation and cost were also identified, consistent with prior studies, particularly among individuals of low socioeconomic status [ 35 , 42 , 43 , 44 , 45 ]. Cost was specifically identified in this study as an especially detrimental barrier for high-risk populations.…”
Section: Discussionsupporting
confidence: 79%
“…For the behavioral skill construct, lack of self-confidence and/or skills to talk about HPV vaccination with sexual partners, relationships with sexual partners, and partners’ vaccine hesitancy were key factors. In addition, issues related to procurement of the vaccine, including perceived unavailability or inaccessibility, were barriers to vaccine uptake; barriers specifically related to transportation and cost were also identified, consistent with prior studies, particularly among individuals of low socioeconomic status [ 35 , 42 , 43 , 44 , 45 ]. Cost was specifically identified in this study as an especially detrimental barrier for high-risk populations.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly a study conducted in Uganda among university students reported high cost of the vaccine as the main reason (63%) for incomplete vaccination (23). Tsachouridou et al (19) and Jochen et al (30) reported free hepatitis B vaccination in Greece and German respectively which could explain a higher uptake compared to our study. Another possible explanation for the variation in vaccination rates is how differently vaccination status was determined.…”
Section: Discussionsupporting
confidence: 49%
“…Despite the Uganda MoH recommendation of HBV vaccination for all PWH (28), only 30.9% were fully vaccinated at Gulu Hospital. Moreover, this proportion was lower than that reported among PWH in Northern Greece (73.6%) (24) South Korea (75%) (29) and German (75.3%) (30). Possible explanation for the difference in vaccination is, a low-income country like Uganda might struggle to maintain a consistent supply of vaccines due to nancial constraints in purchase, transportation and administration of vaccines leading to a lower vaccine coverage.…”
Section: Discussionmentioning
confidence: 78%
“…A recent German study published in 2021 analyzed the rates among PLWH older than 50 years for certain vaccinations including Hepatitis A and B, Influenza, Neisseria meningitidis and Streptococcus pneumonia, as well associated factors for vaccination [12]. The results obtained through this investigation showed similar results for vaccination coverage compared to our study population except for Neisseria meningitidis (51.0%), where utilization of vaccination was remarkably higher potentially as a result of a higher average duration of HIV infection and a higher proportion of men who have sex with men in the sample size.…”
Section: Discussionmentioning
confidence: 99%